THE ROLE OF SADC INSTITUTIONS IN IMPLEMENTING SADC TREATY PROVISIONS DEALING WITH REGIONAL INTEGRATION - Amos Saurombe (Potchefstroom Electronic Law Journal, 2012)
Without some level of institutionalisation or other means of enforcement, national commitment to regional trade integration is bound to face some challenges. Accordingly, transnational trade is obviously inhibited when the validity and enforcement of contracts, obligation and rules cannot be guaranteed beyond the term of office of an administration. Thus Member States' commitment to the work of institutions within a regional economic community like SADC is critical for the full implementation of the SADC Treaty and its Protocols. The Protocol on Trade has been hailed as the most important for integration in SADC. This paper will indicate that institutions are essential drivers of organisations and their role in regional integration is therefore very important. However under the current legal and institutional framework, the SADC regional integration agenda faces major challenges of implementation. SADC institutions are not capable of completely fulfilling their legal obligations, although in some instances the lack of fulfilment was clearly a result of the legal instruments themselves being incomplete and needing further reform.